AI Drives Optimization of Delivery Systems Engineered for Precise and Effective Immune-Based Solutions - P, Divya Bharathi; Murali, S.; Gnanaprakasam, C.; Reenadevi, R.; Madhubala, P.; Mythili, R. (Trends in Immunotherapy, 2026)
In oncology, the development of intelligent, biocompatible nanocarriers is pivotal for advancing targeted immunotherapy. This study presents a protein-binding immunotherapy model that leverages targeted immune proteins, such as interleukins, interferons, and checkpoint inhibitors, integrated with a drug delivery system (DDS). The proposed Zn²⁺-glutamic acid (Glu) nanocarrier, optimized via the AI-based DeepChem platform, demonstrated strong therapeutic potential for cancer treatment. Computational analysis revealed high coordination stability of the Zn²⁺-Glu complex (binding energy: −42.8 kcal/mol) and notable protein-binding affinity to interleukin-2 (IL-2) (7.9 ± 0.3 pKd) using a graph convolutional network model. The nanocarrier achieved efficient protein encapsulation (85.6 ± 2.2%), pH-sensitive release (68.4 ± 1.7% at pH 6.5 over 12 h), and favorable solubility (log S = −1.8). Non-toxicity prediction indicated 92% safety with a ROC-AUC of 0.89. Immunological assays showed a 3.5-fold increase in CD8⁺ T-cell activity, with nanoparticle stability confirmed by a zeta potential of −22.5 mV and PDI of 0.18. Additional benefits included fluorescence traceability at 650 nm and a 2.3-fold increase in systemic half-life, supporting its theranostic capability. Importantly, the Zn²⁺-Glu platform exhibited immunomodulatory and anti-inflammatory properties, suggesting potential to enhance chemotherapy tolerance by reducing systemic inflammation and minimizing immune-related adverse effects. Integrating bioactive components, such as Moringa Leaf Extract (MLE), could further enhance immune cell function while mitigating chemotherapy-induced immunotoxicity. Overall, the Zn²⁺-Glu nanocomposite offers a scalable, non-toxic, and site-specific DDS, positioning it as a promising next-generation protein-derived immunotherapeutic agent.